Kompetensi Guru Pendidikan Agama Islam Dalam Pelaksanaan Evaluasi Pembelajaran - Ismail Anas (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Abstract Competency Islamic Religious Education teachers in implementing the evaluation of learning to determine the competence of teachers of Islamic Education related to evaluation of teaching, and to investigate the evaluation of Islamic Education in schools. Teacher competence is the ability, expertise and skills to be possessed by the teacher in carrying out the learning process that includes learning plan, the implementation of learning until the evaluation. In terms of evaluation, a teacher said when understanding the technical competence and evaluation procedures, and able to carry out the evaluation in order to get the results of evaluation. used to improve the learning process. Implementation of the evaluation is started from evaluation planning, manufacturing test, process and analyze test results to interpret and act on evaluation results.